Correction: Recent progress in controlled nano/micro cracking as an alternative nano-patterning method for functional applications. Issue 7 (11th June 2020) - Jung, Jinwook; Kim, Kyun Kyu; Suh, Young. D.; Hong, Sukjoon; Yeo, Junyeob; Ko, Seung Hwan
Abstract : Correction for 'Recent progress in controlled nano/micro cracking as an alternative nano-patterning method for functional applications' by Jinwook Jung et al., Nanoscale Horiz., 2020, DOI: ; 10.1039/D0NH00241K .